(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The aim of this paper is to find the relation between material parameters and insertion loss of different fabrics using statistical analysis. This research primarily deals with the sound absorption analysis of different uncoated and coated woven textiles fabrics used for curtains as household textiles. The analysis of surface morphology was done by scanning electron microscopy to determine the significance of surface structure onto the sound insulation property. The acoustic properties were measured by reverberation method. The maximum sound insertion loss, minimum sound insertion loss, over all sound insertion loss and percentage improvement in sound insertion loss has been discussed and suggested the woven textiles to be better sound absorber at higher frequencies. Moreover, the effect structural parameters on average sound insulation index were analyzed using SPSS software. The results revealed that warp density, linear density of warp yarn, thickness are influential parameters for the sound insulation property of uncoated fabric whereas the areal density, linear density of warp yarn and thickness influence the sound insulation property coated fabrics.